Blood Flow Restriction Therapy and Its Use for Rehabilitation and Return to Sport: Physiology, Application, and Guidelines for Implementation - Daniel J. Cognetti, M.D; Andrew J. Sheean, M.D; Johnny G. Owens, M.P.T (Elsevier, 2022)
Blood flow restriction (BFR) is an expanding rehabilitation modality that uses a tourniquet to reduce arterial inflow and occlude venous outflow in the setting of resistance training or exercise. Initially, this technique was seen as a way to stimulate muscular development, but improved understanding of its physiologic benefits and mechanism of action has allowed for innovative clinical applications. BFR represents a way to decrease stress placed on the joints without compromising improvements in strength, whereas for postoperative, injured, or load-compromised individuals BFR represents a way to accelerate recovery and prevent atrophy. There is also growing evidence to suggest that it augments cardiovascular fitness and attenuates pain. The purpose of this review is to highlight the physiology and evidence behind the various applications of BFR, with a focus on postoperative rehabilitation. While much remains to be learned, it is clear that blood flow restriction therapy stimulates muscle hypertrophy via a synergistic response to metabolic stress and mechanical tension, with supplemental benefits on cardiovascular fitness and pain. New forms of BFR and expanding applications in postoperative patients and athletes hold promise for expedited recovery. Continued adherence to rehabilitation guidelines and exploration of BFRs physiology and various applications will help optimize its effect and prescription. Level of Evidence: V, expert opinion.